2013
DOI: 10.1002/ceat.201200694
|View full text |Cite
|
Sign up to set email alerts
|

K‐Promoted Hydrotalcites for CO2 Capture in Sorption Enhanced Reactions

Abstract: Potassium‐promoted hydrotalcite‐like material was prepared with potassium nitrate as the K precursor. The highest ever reported CO2 adsorption capacity (1.13 mol kg–1) was obtained at 656 K with p CO 2 = 0.5 bar at humid conditions. A mathematical model was developed and it satisfactorily simulated the adsorption and desorption processes. The stability of the material was tested with repeated adsorption/desorption cycles; the CO2 adsorption capacity decreased around 7 % after ten cycles. In addition, regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
70
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 35 publications
9
70
0
Order By: Relevance
“…One of the most promising techniques for CO 2 suitable materials are known to have good capacities for the sorption of CO 2 at high temperatures: CaO-based materials [5][6][7], hydrotalcites (HT) [2,4,8,9] and lithium based materials [10,11]. Activated carbons and zeolites have been widely used, though the low equilibrium temperature for adsorption (25-150°C) limits their application.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most promising techniques for CO 2 suitable materials are known to have good capacities for the sorption of CO 2 at high temperatures: CaO-based materials [5][6][7], hydrotalcites (HT) [2,4,8,9] and lithium based materials [10,11]. Activated carbons and zeolites have been widely used, though the low equilibrium temperature for adsorption (25-150°C) limits their application.…”
Section: Introductionmentioning
confidence: 99%
“…Sorption Enhanced Water-Gas Shift (SEWGS) is also carried out in a similar fashion, but at temperature lower than conventional WGS reactors (Walspurger et al, 2010;van Dijk et al, 2011;van Selow et al, 2009a;Boon et al, 2014a;van Selow et al, 2009b;Walspurger et al, 2011). The key benefits of SER concepts include cost reduction due to competitive yield with high purity at lower reaction temperature, elimination of carbon formation and catalyst deactivation, and reduction in steam requirement (Wu et al, 2013;Hufton et al, 1999;Li et al, 2006;. In order to be applied to SER process applications, the sorbent materials should possess a sufficiently high and reversible CO 2 capacity in the temperature range of 200e500 C and in the pressure range of 1e40 bar, fast kinetics, and a good mechanical and thermal stability under employed operating conditions OchoaFernandez et al, 2006a).…”
Section: Significance Of Htlcs and Metal-based Oxidesmentioning
confidence: 97%
“…They also considered the recovery of CO2 as a combination of a fast desorption step and a slower desorption step. Wu Y. J. et al [8] heated fixed-bed reactor from 383 to 435 o C for a faster CO2 release. Hanif A. et al [9] found that evacuation could be used to achieve a faster regeneration.…”
Section: Introductionmentioning
confidence: 99%